A LINGUISTIC STUDY OF CORRELATIVE CONJUNCTIONS IN ENGLISH AND VIETNAMESE DISCOURSE - Phạm Ái Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The thesis is designed to investigate the semantic and syntactic features of correlative conjunctions in English and Vietnamese discourse. In order to do this, the following theoretical as well as practical matters are taken into consideration in this thesis. In theoretical background, we have collected examples in English and Vietnamese discourse, analyzed them and find out their similarities and differences in English and Vietnamese of correlative conjunctions in view of syntactic features and semantic values. This careful investigation might lay foundations to suggest some implications for English and learning as well as translation work in Vietnam. This helps Vietnamese learners of English achieve better communicative competence.